IDENTIFIKASI MODAL POLITIK DAN MODAL SOSIAL ANGGOTA LEGISLATIF DARI KALANGAN AKADEMISI PADA PEMILU LEGISLATIF KABUPATEN SUMBAWA TAHUN 2024 - Irawansyah, Irawansyah; Randi Afriadi (Nusantara Hasana Journal, 2025)
Political capital and social capital refer to a number of resources, both real and potential, owned by individuals or groups. These resources come from a network of sustainably established relationships, most of which have been institutionalized. Political capital can be defined as the use of various types of capital owned by a political actor or institution, to create profitable political actions and strengthen their position. Political capital is a crucial element in the political process, both in the context of general elections and in efforts to make structural changes. When managed and used properly, the social and political capital owned by individuals can provide many benefits. This study adopts a qualitative approach, which focuses on analyzing the inductive thinking process related to the dynamics of the relationship between observed phenomena, while still applying scientific logic. This type of research is qualitative descriptive, which aims to understand various existing problems and applicable work procedures. The data collected by the researcher was in the form of written and oral words from informants. For this reason, the researcher conducted interviews with academics who are running for members of the Sumbawa Regency DPRD in the 2024 election. Social capital and political capital are forces that can build strong networks and relationships with the community, encouraging them to actively participate in supporting legislative candidates. This interaction is established through various joint activities, such as social and religious events, assistance to the local community, and daily interactions. The social relationships that have been formed are a valuable asset for legislative candidates in determining their position in the environment they want to control as a vote base.